PENGEMBANGAN MEDIA PEMBELAJARAN KIMIA BERBASIS LECTORA INSPIRE 12 PADA POKOK BAHASAN HIDROKARBON KELAS XI MIA SMA/MA - Fatmawati, Vita; Copriady, Jimmi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of this research was to develop media of chemistry learning in hydrocarbon based on Lectora Inspire 12. The method used was Research and Development (R&D) with ADDIE model which was consists of five stages are analysis, design, development, implementation and evaluation. The collecting data used validation sheet were given to three validators (two of matter experts and a media expert) and questionnaire for teacher and student. The result of validation showed that the percentage of pedagogic, content, designing and the convenience aspects consecutively was 95%; 97,22%; 93,18% and 100% with the average 96,35% (valid). The pilot study was conducted on three teachers and 20 students in grade XII IPA 3 SMA PGRI Pekanbaru. The result study show with consecutively were 89,44% (teachers) and 90,33% (students) in good category.Key Words: Learning Media, Lectora Inspire 12, Hydrocarbon